Use of micro-analysis to augment the macro-archaeological investigation of an elevated Holocene shell midden, Dampier Archipelago, NW Australia - Ward, I; McDonald, J; Monks, C; Fairweather, J (Frontiers in Earth Science, 2022)
Few studies in Australia have employed automated mineral techniques to augment archaeological site investigations, and there are no known published micromorphological studies of Australian shell midden sites. This pilot study presents results of a micro-analytical investigation of a Tegillarca granosa (formerly known as Anadara granosa) midden in the Old Geos site, located in an elevated location on the Burrup Peninsula in NW Australia. Analytical investigations were undertaken on a 15 cm profile in the upper section dated to 1,500 cal yr BP of a 50 cm excavation profile that has a maximum age estimate of around 7,000 cal yr BP. Although invertebrate activity has reduced the temporal and spatial resolution, mineralogical analyses differentiate a higher relative concentration of alkali feldspars in the top of the sampled profile consistent with freshly weathered granophyre bedrock, as well as presence of rare rutilitic quartz. The profile otherwise shows sediment source and transport has remained constant. In addition to the shell, cultural material includes fish, mammal and possibly avian bone, some of which have been burnt. Plant material is limited but does include micro-fragments of charcoal and phytoliths from grass and wood. Fungal tissue is further evidence of present or past degrading organic matter. Both this, and a previous micro-analytical study on the more distant site of Barrow Island, highlight how micro-analytical investigation can provide more detail on depositional and post-depositional history of midden and other archaeological records in this region.